A virtual fixture using a FE-based transformation model embedded into a constrained optimization for the dimensional inspection of nonrigid parts. (May 2015) - Abenhaim, Gad N.; Desrochers, Alain; Tahan, Antoine S.; Bigeon, Jean
Abstract: Virtually mounting nonrigid parts onto their fixture is proposed by researchers to remove the need for the use of complex physical inspection fixtures during the measurement process. Current approaches necessitate the pre-processing of the free-state nonrigid part's point cloud into a suitable finite element (FE) mesh and are limited by the use of the boundary conditions setting methods available in FE software. In addition to these limits, these approaches do not take into account the forces used to restrain the part during the inspection, as commonly mandated for aerospace panels. To address these shortcomings, this paper presents a virtual fixture method that predicts the fixed shape of the part without the aforementioned drawbacks of current approaches. This is achieved by embedding information retrieved from a FE analysis of the nominal CAD model into a boundary displacement constrained optimization. To evaluate the proposed method, two case studies on physical parts are performed using the proposed virtual fixture method to evaluate the profile and assembly force specifications of each part. Highlights: The virtual fixture method allows for the inspection of nonrigid parts. It does not necessitate the pre-processing of the point cloud into a FE mesh. It takes into account the part's specification limiting the restraining forces. It infers the part's structural behavior from the FE model of the nominal CAD. Two case studies on physical parts are performed.